Evaluation of road traffic noise near tube-shaped bus rapid transit shelters - Santos, Geanesson Alberto de Oliveira; Nascimento, Eriberto Oliveira do; Zannin, Paulo Henrique Trombeta (Revista Nacional de Gerenciamento de Cidades, 2021)
Noise pollution is generally imperceptible, but it can cause various disorders, including psychological disorders, hearing loss and cardiovascular disease. Curitiba Municipal Law 10.625:2002 establishes upper limits of daytime noise exposure according to zoning areas and land use in the City of Curitiba. The purpose of this study was to evaluate noise immissions of urban traffic in the proximities of Bus Rapid Transit (BRT) shelters in Curitiba, Brazil. Daytime traffic noise levels were measured between 8am and 5pm near the entrance of these bus shelters in July and August 2014. Fifty-four measurement points at parks, residences, stores, schools, universities and hospitals in different zoning groups of the municipality were selected as a function of the type of population. The noise levels were recorded using a class I sound level meter. Brazil has no specific standard or law for traffic noise immissions, so the guidelines of the Brazilian standard ABNT NBR 10151:2000 were used. It was concluded that 74% of the measured noise levels varied from 70 to 76 dB(A). Only point 48, close to the Antônio Meireles Sobrinho BRT Shelter, was considered free of noise pollution. Traffic noise accounts for an overall average of 73 dB(A). A few bus shelters installed on the same street had an absolute average difference of 3 dB(A), while bus shelters located farther away from roads were the least noisy. The lowest average traffic noise levels, i.e., 71 dB(A), were recorded on roads for exclusive use by BRT buses.